INGLIZ TILIDAGI EVFEMIZMLARNING PRAGMATIK XUSUSIYATLARI - Rahmonova, Gulhayo Xalilovna (Innovative Development in Educational Activities, 2023)
Currently, in a globalized society the need for word substitutions while speaking on sensitive topics has developed. Human beings search for milder alternatives to express their opinions whenever they feel their words might sound abrupt or offensive. The article illustrates these substitutions called euphemisms. At first sight one might suppose that these expressions are too ordinary, but in fact they possess a strong persuasive character. Thus, the subject of this article is to identify the main functions of euphemisms in modern society. The article also aims at determining which social and cognitive factors regulate our choice of these substitutions. In the article as data for analysis different euphemistic expressions have been studied. An overall study shows that in modern life honest debate has turned into a rare phenomenon. One of our assertions is that the use of euphemisms primarily presupposing good intentions so as not to hurt a listener’s feelings, in modern life has acquired completely a different purpose. Today people use euphemisms to sound more persuasive instead of simply sounding polite. It should be noted that for a deeper understanding of the role of euphemisms they should be studied within a specific discourse.